Design and Build a Village-level Government Medium-term Development Plan (RPJM) Information System - Rosada, Amrina; Widya, Moh Anshori Aris (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The village medium-term development plan (RPJM desa) is one of the development planning documents that is required to be prepared for the village-level government by Law number 25 of 2004 concerning the National Development Planning System in the law which also mandates that 3 (three months after the head of the village is inaugurated the preparation of the village medium-term development plan (RPJM desa) must be completed and determined. In this study, the author uses the website as an information system for the Village Government's Medium Term Development Plan to design an RPJM and carry out development activities needed by the village.